Images syndicales du travail cheminot. Les archives photographiques du Landesverband au Luxembourg - Sébastien Moreau (Images du Travail, Travail des Images)
Trade unions produce, preserve and disseminate images of the labour market and of the workers they defend and whose collective memory they safeguard. By studying the photographic archives of the Landesverband, a major railway workers' union in Luxembourg, this article aims to give an account of the reasons for and methods of producing and disseminating trade union iconography relating to the railway sector. This study is all the more relevant in that the union and its visual relationship with railway workers are currently being renewed, at a time when photographic collections are being digitised, web 2.0 is burgeoning and projects are underway to write history and make railway workers' memories part of the common cultural heritage.